Nutritional strategies against dementia in rural populations - Goncalves, Bruno S.; Gannavaram, Naga L.; Yates, Cohen; Kandula, Aishniya; Nayyar, Aleen; Pillai, Sneha S.; Puri, Ridhi K.; Nayyar, Asma (Frontiers in Nutrition, 2025)
Dementia is a progressive neurodegenerative disorder that represents a growing challenge to global health, especially in aging populations. The burden of dementia is high in rural communities, where access to healthcare services, nutritional resources, and educational opportunities is significantly limited. A critical knowledge gap exists regarding how rural-specific nutritional disparities mechanistically interact with gut–brain axis dysfunction to influence dementia risk. The gut-brain axis mediates neuroimmune communication, metabolic regulation, and microbial signaling, and nutritional insufficiency is associated with reduced microbial diversity, impaired short-chain fatty acid (SCFAs) production, increased intestinal permeability, and heightened systemic inflammatory activity, all of which contribute to neurodegenerative processes. This review delineates the mechanistic pathways linking malnutrition-induced gut dysregulation to neuronal injury and cognitive decline, with a specific focus on rural populations. We further evaluate the biological actions of key nutraceutical classes, including phytochemicals (curcumin, resveratrol, sulforaphane, ginkgo biloba), vitamins (B12, C, E, and D), and metabolic/dietary interventions (omega-3 fatty acids, ketogenic diet, Mediterranean diet, trehalose). By consolidating preclinical and clinical evidence, we identify the molecular targets through which these nutraceuticals modulate oxidative stress, inflammatory signaling networks, blood-brain barrier (BBB) integrity, and microRNA regulation. In summary, our findings suggest that nutraceutical-based approaches targeting gut-brain axis dysfunction may provide a feasible and biologically informed strategy for mitigating dementia disparities in rural settings.